Faces d'a moeda do tempo de Gastão Cruz - Mahmud, Zaira Batista Pinto (2011)
This Dissertation aims to study the book A Moeda do Tempo from Gastão Cruz, published in 2006. Besides this, it focusses ou how the poet builds his poetical language, considering the time as a theme, properly the memory and the death themselves, through the construction of a poetic shape. Thinking the coin as an allegory includes to consider its most varied meanings, and this study aims in a way of reading to expand possibilities instead of limiting them.